RIGHT VENTRICULAR AND PULMONARY HYPERTENSION IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND RESTRICTIVE LUNG DISEASE - Valencia Fabiana; Dwi Lestari Partiningrum; Bernardus Parish Budiono; Fathur Nur Kholis (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Chronic lung disease is frequently associated with lung vascular lesion. We evaluated the structural-functional related changes of right ventricle under CLD with or without PH at RSUP dr. Kariadi, Semarang. Methods: We studied patients at RSUP dr. Kariadi who underwent routine evaluation that included resting spirometry and echocardiography. Patients with either COPD or RLD were studied, exclusion were made for patients with valvular heart disease and congestive heart disease. This study was performed during May through June of 2019 (n = 20). PASP, RVD, RVWT, TAPSE and spirometry values were analyzed for the association between PASP and RVD, RVWT, TAPSE, TAPSE/PASP ratio and FVC, FEV1, FEV1/FVC. Results: Thirteen (65%) of 20 patients who underwent echocardiography and spirometry evaluation were male and their average age were 55 years old. Mean PASP was 49.30 mmHg (range 2–111 mmHg). Ninety five percents patients had restrictive spirometry and 5% patients had moderate-severe mixed spirometry. The majority of the population of the study sample is dominated by a very severe degree of restriction spirometry. Out of the 20 subjects, 15 subjects (75%) had a diagnosis of COPD and 10 subjects (50%) had a history of pulmonary TB. In this study, 75% subjects had right ventricular dilatation, 85% subjects had right ventricular hypertrophy, and 15% subjects had decreased right ventricular systolic function (low TAPSE). The majority of structural and functional abnormalities of the right heart are found on patients with very severe degree of restriction spirometry. There were 13 subjects (65%) pulmonary hypertension, with the most findings being severe pulmonary hypertension as many as 8 subjects (40%). As many as 14 subjects (70%) had high TAPSE / PASP ratio.Conclusions: PH prevalence in patients with CLD is significantly associated with spirometry values. PH severity degree in patients with CLD is not significantly associated with spirometry values.Key words: spirometry; pulmonary hypertension; right heart echocardiography.